Trade in Developing East Asia : How It Has Changed and Why It Matters - Constantinescu, Cristina (World Bank, Washington, DC, 2018)
East Asia, for long the epitome of successful engagement in trade, faces serious challenges: technological change that may threaten the very model of labor intensive industrialization and a backlash against globalization that may reduce access to important markets. A detailed analysis of the evolution of East Asia's trade and trade policy in goods and services leads to the conclusion that how East Asia copes with these global challenges will depend on how it addresses three more proximate national and regional challenges. The first is the emergence of one East Asian country, China, as a global trade giant—accounting for nearly one-seventh of global exports and one-tenth of global imports -- which is fundamentally altering the trading patterns and opportunities of its neighbors. The second is the asymmetric implementation of national reform -- remarkable openness to goods trade and investment coexists with relative restrictiveness of services policies -- which is affecting the evolution of comparative advantage and productivity in each country. The third is the divergence between the relatively shallow and fragmented agreements that regulate the region’s trade and investment and the growing importance of regional and global value chains as crucial drivers of productivity growth.